Knowledge and Practice of Nurses and Associated Factors in Managing Neonatal Pain at Selected Public Hospitals in Addis Ababa, Ethiopia, 2020 - Wari G; Wordofa B; Alemu W; Habte T (Journal of Multidisciplinary Healthcare, 2021)
Gemechis Wari, Berhanu Wordofa, Wudma Alemu, Teshome Habte Department of Nursing, School Nursing and Midwifery, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Teshome Habte Tel +251 911436150Email teshome.habte@aau.edu.et; teshomeh497@gmail.comIntroduction: Hospitalized neonates experience moderate to severe, acute or chronic pain. Recent study indicates that health care providers especially in developing countries have a knowledge and skills gap related to neonatal pain management.Objective: The aim of this study was to assess the neonatal ICU nurses’ knowledge and practice and factors associated with neonatal pain management at selected public hospital of Addis Ababa, Ethiopia.Methods: Facility-based cross-sectional study design was employed at four selected public hospitals in Addis Ababa, from April to May 2020. A simple random sampling method was used to recruit study participants using a semi-structured and self-administered questionnaire. The logistic regression model was used to identify the association, and odds ratio was used to test the strength of the associations between outcome and predictor variables.Results: This study was conducted with 119 nursing staffs working in the neonatal intensive care unit with a 96.6% response rate. The study reveals that 68.7% of nurses had adequate knowledge and only 32.2% of them had good practice of neonatal pain management. There was a significant relationship between nurses’ knowledge scores and receiving in-service training on neonatal pain management. Having an infant pain management policy in place, getting training on neonatal pain management and knowledge category were factors significantly associated with practice of nurses in neonatal pain management.Discussion: According to the results of the current research, the majority (85.2%) of participants knew that the vital signs of new-borns can be affected by pain. However, only 60.9% of nurses considered pain as one of the vital signs in new-borns. This indicates that neonatal pain may not be assessed as frequently as a vital sign. And the finding reveals that nurses had poor practice but had adequate knowledge in managing neonatal pain. The respective hospitals and Ethiopian Ministry of Health should provide gap-filling training on neonatal pain management to the nurses.Keywords: pain, management, neonatal intensive care unit, knowledge, practice, nurses